Konstruksi Hukum Islam Berbasis Tradisi Lokal di Kalangan Masyarjah Tradisionalis Situbondo: The Construction of Islamic Law Based on Local Tradition Among the Traditionalist Community of Situbondo - Ishaq Ishaq (Fenomena, 2018)
The crucial phenomenon addressed is the tension between Islamic law and local traditions in Situbondo, where traditionalist Muslims face accusations from radical and reformist groups of losing Islamic authenticity due to cultural assimilation. This study is situated within the broader theoretical debate on al-‘Urf (local custom) and the need for a paradigm shift in Islamic legal epistemology from dogmatic repetition to revolutionary discovery. The research aims to analyze how the progressive santri community in Situbondo constructs Islamic law based on local traditions such as Paron and Duun Tarakat. A qualitative, descriptive-analytical approach with an epistemological framework inspired by Thomas Kuhn’s paradigm shift was employed, focusing on empirical and philosophical levels of analysis. The findings reveal that the community builds Islamic law on a dialogical-symbiotic process between universal Islamic values (justice, benefit) and the substantive meanings of local traditions, prioritizing universal meanings over textual literalism. The study concludes that this post-dogmatic construction represents a genuine paradigm shift from normal science to revolutionary science, producing moderate, multicultural, and humanistic legal products, and recommends adopting such contextual methodologies in formulating future positive law in Indonesia. Fenomena krusial yang diangkat adalah ketegangan antara hukum Islam dan tradisi lokal di Situbondo, di mana masyarakat santri tradisionalis dituduh kelompok radikal dan reformis kehilangan otentisitas Islam karena akulturasi budaya. Penelitian ini berada dalam peta besar teori al-‘Urf dan perlunya pergeseran paradigma dalam epistemologi hukum Islam dari pengulangan dogmatis menuju penemuan revolusioner. Penelitian bertujuan menganalisis bagaimana santri kalangan progresif Situbondo mengkonstruksi hukum Islam berbasis tradisi lokal seperti Paron dan Duun Tarakat. Metode yang digunakan adalah penelitian kualitatif deskriptif-analitis dengan pendekatan epistemologi filsafat ilmu, khususnya gagasan pergeseran paradigma Thomas Kuhn, serta menekankan pada tataran empiris. Hasil penelitian menunjukkan bahwa konstruksi hukum Islam dibangun melalui proses dialogis-simbiosis antara nilai-nilai universal Islam (keadilan, kemashlahatan) dengan nilai substansial tradisi lokal, mengutamakan makna universal teks而非 tekstual. Kesimpulannya, konstruksi post-dogmatik ini merupakan pergeseran paradigma menuju revolutionary science, menghasilkan produk hukum moderat, multikultural, dan humanis. Rekomendasinya, metodologi kontekstual semacam ini perlu diadopsi dalam penyusunan hukum positif di masa depan.